On the stability of the passive Ti-6Al-4V film of friction stir welds with stainless steel: Effect of not native metal species - Silva, Diego D.; Campanelli, Leonardo Contri; Bergmann, Luciano; dos Santos, Jorge F.; Hammer, Peter [UNESP]; Rovere, Carlos A. Della; Aquino, José M. (Elsevier, 2020)
Mechanical and microstructural characteristics of Ti-6Al-4V/stainless steel (SS) dissimilar friction stir welds have been well described in the literature; however, little is known about the electrochemical properties of such welds in terms of the passive film stability of TiO2 grown in oxidizing media. To clarify this issue, potentiodynamic polarization, cyclic voltammetry, and electrochemical impedance measurements were carried out in the Ti-6Al-4V alloy to analyze the effects of Fe and Cr contamination from the underlying SS on the passive film stability of TiO2 in concentrated (6.0 and 11.5 mol L–1) HNO3 solutions. Lower transpassive potentials were observed for samples in the stirred zone (SZ) than those of the base metal (BM) due to Fe and Cr contamination. Anodic charges obtained during cyclic voltammetry using 6.0 mol L–1 HNO3 showed that the grown passive film was completely dissolved and regrown after consecutive scans, except for the BM sample. According to the results of X-ray photoelectron spectroscopy (XPS) analyses an Al depleted layer was obtained for the latter condition, which confirms the stability of TiO2 film. The increasing values of charge transfer resistance obtained through electrochemical impedance measurements at distinct potentials in the passive region also supported the stability of the TiO2 film grown in 6.0 mol L–1 HNO3 solution. The formation of a medium frequency inductive loop and low frequency constant phase element are related to the dissolution of the oxide film and adsorption of NO3 species into the formed passive film, respectively, as evidenced by XPS analyses.
Keywords: Adsorption of electrolyte species; Inductive loop; Solid-state welding; Surface reconstruction; TiO2 film stability